AB0287 HEMATOLOGICAL SIDE EFFECTS OF BIOLOGICAL THERAPY IN RHEUMATOLOGY: DATA FROM THE TUNISIAN REGISTER. (13th June 2020) - Bettaieb, H.; Boussaid, S.; Jemmali, S.; Rekik, S.; Cheour, E.; Sahli, H.; Elleuch, M.; Abdelmoula, L.; Laatar, A.; Hamdi, W.; Kochbati, S.; Bouajina, E.; et al.
Abstract : Background: During the last decade, the treatment of chronic inflammatory rheumatism (CIR) has been greatly improved with the advent of biotherapy.However, the use of biological treatment can lead to a number of side effects including abnormalities in the blood count. Objectives: The aim of this study was to assess the different hematological side effects of biological treatment in patients with rheumatoid arthritis (RA) and spondyloarthitis (SA). Methods: This study included patients with RA (ACR/EULAR 2010) and SA (ASAS 2009) registred with the Tunisian Biologic National Registry (BINAR).Patients were followed and treated with biologics for 2 years of less. Clinical data relative to biological treatment, including haematological side effects, have been collected. Results: Two hundred and ninety-eight patients (178 women and 111 men) were included in the study. The mean age was 49.2 ± 14.1 years. The male/female ratio was 0.6. The mean diseases durations for RA and SA were respectively 6.7 ± 3.5 years and 6.5 ±3.6 years. Anti-TNFα agents were prescribed in 87.9% of patients (n = 263) with respectively: Infliximab (20.4%) Etanercept (23.1%), Adalimumab (24.6%) and Certolizumab (26.5%). Tocilizumab and Rituximab were prescribed in 10.4% and 5% of the patients, respectively. Blood count abnormalities were noted in 15.4 % of patients (n=46). Neutropenia was the most frequently anomaly met on the hemogram (9.1%) followed by anemia (3.4%) and thrombocytopenia (3%). Pancytopenia was found in 11.4% of patients (n=34). The median time between biological therapy initiation and the onset of hematologic manifestations was 4.8 months [1-12]. Biological treatment was interrupted in two patients. In the other cases, the biological treatment was maintained with close monitoring of blood cell count. No case of death related to these hematological disturbances has been reported. Conclusion: In our registry, hematological side effects of biological treatment were found in 15.4% of cases and were noted with a median delay of 4.8 [1-12] months after the treatment initiation. Further studies are needed to confirm our preliminary results. Disclosure of Interests: None declared